1999
DOI: 10.1111/j.1469-7793.1999.897ab.x
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of placental and fetal growth in sheep alters fetal blood pressure responses to angiotensin II and captopril

Abstract: A series of epidemiological studies have described a relationship between low birth weight and high blood pressure in adult life and have proposed that factors associated with restriction of growth in utero act to reprogramme the development of the cardiovascular system which leads to the emergence of hypertension in adult life (Barker et al. 1990; Barker, 1992). It has also been demonstrated in pregnant rats that maternal protein restriction results in high blood pressure in the growth restricted offspring (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(160 citation statements)
references
References 33 publications
8
152
0
Order By: Relevance
“…However, this period of elevated plasma renin activity corresponded to a relative hypotension in the IUGR lambs; this raises the possibility that the increased plasma renin activity was a response to the lower arterial pressure. A recent study (30) found no difference in the MAP of control and IUGR fetuses (following carunclectomy); however, these two groups of animals responded differently to captopril (ACE inhibitor) and angiotensin II infusions. These results (30) suggest that arterial pressure in IUGR fetuses may be regulated by the renin-angiotensin system in a manner different to that in normal fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…However, this period of elevated plasma renin activity corresponded to a relative hypotension in the IUGR lambs; this raises the possibility that the increased plasma renin activity was a response to the lower arterial pressure. A recent study (30) found no difference in the MAP of control and IUGR fetuses (following carunclectomy); however, these two groups of animals responded differently to captopril (ACE inhibitor) and angiotensin II infusions. These results (30) suggest that arterial pressure in IUGR fetuses may be regulated by the renin-angiotensin system in a manner different to that in normal fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Pentothal; Rhone Merieux, Pinkenba, Qld Australia) and maintained with halothane (2.5-4% Fluothane; ICI, Melbourne, Vic, Australia) in oxygen. Vascular catheters were inserted into a fetal carotid artery and jugular vein, the maternal jugular vein and into the amniotic cavity as previously described (Edwards et al 1999). Vascular catheters were inserted into one fetus in twin pregnancies.…”
Section: Embryo Transfer and Pregnancy Monitoringmentioning
confidence: 99%
“…In fetal and neonatal sheep, hemorrhage and hypovolemia increase circulating angiotensin II (Ang II) (5)(6)(7). Although inhibition of Ang II receptors (AT) or converting enzyme accentuates hypovolemic episodes (3,7), their effects on basal arterial pressure are inconsistent (8,9). AT blockade also modifies the baroreflex and reflex control of renal sympathetic nerve activity after birth (10,11).…”
mentioning
confidence: 99%